Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine whether each given function is an odd function, we need to use the definition of odd functions. A function [tex]\( f(x) \)[/tex] is considered odd if [tex]\( f(-x) = -f(x) \)[/tex] for all values of [tex]\( x \)[/tex]. Let's analyze each function one-by-one.
1. For [tex]\( f(x) = -x^2 + 3x - 2 \)[/tex]:
[tex]\[ f(-x) = -(-x)^2 + 3(-x) - 2 = -x^2 - 3x - 2 \][/tex]
[tex]\[ -f(x) = -(-x^2 + 3x - 2) = x^2 - 3x + 2 \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ -x^2 - 3x - 2 \neq x^2 - 3x + 2 \][/tex]
Therefore, [tex]\( f(x) = -x^2 + 3x - 2 \)[/tex] is not an odd function.
2. For [tex]\( f(x) = -3x \)[/tex]:
[tex]\[ f(-x) = -3(-x) = 3x \][/tex]
[tex]\[ -f(x) = -(-3x) = 3x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = 3x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = -3x \)[/tex] is an odd function.
3. For [tex]\( f(x) = 2x^3 + x \)[/tex]:
[tex]\[ f(-x) = 2(-x)^3 + (-x) = -2x^3 - x \][/tex]
[tex]\[ -f(x) = -(2x^3 + x) = -2x^3 - x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = -2x^3 - x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = 2x^3 + x \)[/tex] is an odd function.
4. For [tex]\( f(x) = -9x \)[/tex]:
[tex]\[ f(-x) = -9(-x) = 9x \][/tex]
[tex]\[ -f(x) = -(-9x) = 9x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = 9x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = -9x \)[/tex] is an odd function.
5. For [tex]\( f(x) = -4x + 1 \)[/tex]:
[tex]\[ f(-x) = -4(-x) + 1 = 4x + 1 \][/tex]
[tex]\[ -f(x) = -(-4x + 1) = 4x - 1 \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ 4x + 1 \neq 4x - 1 \][/tex]
Therefore, [tex]\( f(x) = -4x + 1 \)[/tex] is not an odd function.
Based on the above analysis, the odd functions among the given options are:
- [tex]\( f(x) = -3x \)[/tex]
- [tex]\( f(x) = 2x^3 + x \)[/tex]
- [tex]\( f(x) = -9x \)[/tex]
So, the correct answers are:
[tex]\( f(x) = -3x \)[/tex], [tex]\( f(x) = 2x^3 + x \)[/tex], and [tex]\( f(x) = -9x \)[/tex].
1. For [tex]\( f(x) = -x^2 + 3x - 2 \)[/tex]:
[tex]\[ f(-x) = -(-x)^2 + 3(-x) - 2 = -x^2 - 3x - 2 \][/tex]
[tex]\[ -f(x) = -(-x^2 + 3x - 2) = x^2 - 3x + 2 \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ -x^2 - 3x - 2 \neq x^2 - 3x + 2 \][/tex]
Therefore, [tex]\( f(x) = -x^2 + 3x - 2 \)[/tex] is not an odd function.
2. For [tex]\( f(x) = -3x \)[/tex]:
[tex]\[ f(-x) = -3(-x) = 3x \][/tex]
[tex]\[ -f(x) = -(-3x) = 3x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = 3x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = -3x \)[/tex] is an odd function.
3. For [tex]\( f(x) = 2x^3 + x \)[/tex]:
[tex]\[ f(-x) = 2(-x)^3 + (-x) = -2x^3 - x \][/tex]
[tex]\[ -f(x) = -(2x^3 + x) = -2x^3 - x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = -2x^3 - x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = 2x^3 + x \)[/tex] is an odd function.
4. For [tex]\( f(x) = -9x \)[/tex]:
[tex]\[ f(-x) = -9(-x) = 9x \][/tex]
[tex]\[ -f(x) = -(-9x) = 9x \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ f(-x) = 9x = -f(x) \][/tex]
Therefore, [tex]\( f(x) = -9x \)[/tex] is an odd function.
5. For [tex]\( f(x) = -4x + 1 \)[/tex]:
[tex]\[ f(-x) = -4(-x) + 1 = 4x + 1 \][/tex]
[tex]\[ -f(x) = -(-4x + 1) = 4x - 1 \][/tex]
Comparing [tex]\( f(-x) \)[/tex] and [tex]\( -f(x) \)[/tex]:
[tex]\[ 4x + 1 \neq 4x - 1 \][/tex]
Therefore, [tex]\( f(x) = -4x + 1 \)[/tex] is not an odd function.
Based on the above analysis, the odd functions among the given options are:
- [tex]\( f(x) = -3x \)[/tex]
- [tex]\( f(x) = 2x^3 + x \)[/tex]
- [tex]\( f(x) = -9x \)[/tex]
So, the correct answers are:
[tex]\( f(x) = -3x \)[/tex], [tex]\( f(x) = 2x^3 + x \)[/tex], and [tex]\( f(x) = -9x \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.